2017
DOI: 10.18203/2320-6012.ijrms20175538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laryngeal mask airway supreme™ versus endotracheal intubation in positive pressure ventilation with muscle relaxant for intraoperative and postoperative conditions

Abstract: Background: Laryngeal Mask Airways are increasingly being used now a day as an option to endotracheal intubation, as it is less invasive and causes less discomfort in the postoperative period. The aim of this study was to evaluate the clinical use of the laryngeal mask airway SupremeTM in patients undergoing elective gynaecological surgeries under general anaesthesia and compare it with endotracheal intubation.Methods: 60 ASA I and II females, having BMI <30kg.m-2 in the range of 20-50 years of age, schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The response produced by laryngoscopy with ETT insertion was significantly greater than that caused by LMAS insertion. Findings of our study were consistent with study conducted by Singham et al [1] who reported that haemodynamic variables at baseline and before insertion were nearly similar in both the groups, however post insertion significantly increased values in HR and mean blood pressure was observed in the ETT group as compared to the LMA group. Similarly significant increase in haemodynamic variables was seen at extubation also.…”
Section: Insertion Timesupporting
confidence: 92%
See 3 more Smart Citations
“…The response produced by laryngoscopy with ETT insertion was significantly greater than that caused by LMAS insertion. Findings of our study were consistent with study conducted by Singham et al [1] who reported that haemodynamic variables at baseline and before insertion were nearly similar in both the groups, however post insertion significantly increased values in HR and mean blood pressure was observed in the ETT group as compared to the LMA group. Similarly significant increase in haemodynamic variables was seen at extubation also.…”
Section: Insertion Timesupporting
confidence: 92%
“…In our study, the mean time required for the insertion of ETT was 26.20±2.33 sec which was significantly more compared to time required for LMA supreme insertion which was 21.00±3.20 sec (p = 0.002). Similar findings were seen in the study done by Singham et al [1] and Mahmood HE et al [17] Haemodynamic changes Our study demonstrated that there was a haemodynamic response consisting of an increase in HR and MAP associated with laryngoscopy and ETT and LMAS during, insertion as well as extubation. The response produced by laryngoscopy with ETT insertion was significantly greater than that caused by LMAS insertion.…”
Section: Insertion Timesupporting
confidence: 91%
See 2 more Smart Citations